Effects of Enol-Imine/Keto-Amine Tautomerism and Conformational Changes on the Electronic Spectra of a Novel 1,2,4-Triazole Ortho-Hydroxyaryl Schiff Base in Different Solvents - Sıdır, İsa; Sıdır, Yadigar Gülseven; Berber, Halil; FAUSTO, RUI (Elsevier, 2023)
In this study, a novel o-hydroxyaryl Schiff base bearing the 1,2,4-triazole heterocyclic core, (E)-2-(((4H-1,2,4-triazol-4-yl)imino)methyl)-6-methoxyphenol, was synthesized and structurally characterized by NMR (1H-and 13C-) and IR spectroscopies as well as by Density Functional Theory (DFT) electronic structure calculations. The compound was then investigated by UV-Vis absorbance and fluorescence emission spectroscopies in different solvents. The wavelength shifts observed in the band corresponding to the lowest energy transition in the absorbance spectra upon changing the solvent, as well as in the emission bands observed in the fluorescence spectra (upon excitation at 310 nm) were explained considering the effects of solvent-induced conformational changes and photoinduced enol-imine/keto-amine tautomerism. The interpretation of the experimental results was supported by structural data calculated for the different isomeric forms of the compound and of their electronic spectra in the gas phase and in solvents of different polarity. Solvent effects were also evaluated at the light of the Kamlet-Taft and Catal & PRIME;an solvatochromic models.
Keywords: Schiff Base; Enol-Imine/Keto-Amine Tautomerism; Solvent Effects; Conformational Changes